Hubungan Antara Sarapan Dengan Daya Tangkap Anak kelompok A Usia 4-5 Tahun di TK Sekecamatan Binawidya Pekanbaru - Ade Yelda Hastriati; Joni Joni (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aimed to determine the association between breakfast and comprehension ability of children aged 4-5 years in Kawunganten, Cilacap. Breakfast was important to study because it affects children’s comprehension ability. The research approach was quantitative approach with correlational research type. The respondent was 113 children. The data were collected by observation techniques and questionnaires. The Questionnaires were about comprehension ability filled by observers and questionnaires about breakfast filled by parents. The instruments already tested with validity and reliability test. The validity was test with expert judgement. Reliability test was used test-retest method. Reliable when between authors with the observer have the same perception about the research object. The research data were analize with product moment correlation. The result showed that the r-value of 0.450. This was higher than the r- table at a significance level of 5% that was worth 0.195. In this study, there was a positive correlation between breakfast and comprehensive ability of children aged 4-5 years old in Kawunganten, Cilacap. The effective contribution of this research was to the comprehensive ability of children aged 4-5 years in the Kawunganten, Cilacap is r2 x 100% ie 20.25%. Keywords: breakfast, comprehension ability, children 4-5 years old